1984
DOI: 10.1093/jac/14.suppl_c.75
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics and tissue penetration of enoxacin and norfloxacin

Abstract: Two new quinoline compounds, enoxacin (600 mg) and norfloxacin (400 mg) were administered consecutively to six healthy male volunteers. The levels of the two agents were measured in serum, urine and blister fluid. The mean peak serum level of enoxacin was 3.7 mg/l and attained at a mean time of 1.9 h after administration; the mean peak serum level of norfloxacin was 1.45 mg/l at a mean time of 1.5 h. The mean serum half-lives were 6.2 h for enoxacin and 3.25 h for norfloxacin. Both agents penetrated blister fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Our results demonstrate a marked ofloxacin presence (53.48 ug/g) greater than that of pefloxacin (22.28 I1g/g) and ciprofloxacin (11.81 ug/g) in the parotid gland and are in agreement with Sorgel's findings of quinolones in the saliva: ofloxacin (0.89) >pefloxacin (0.54) >ciprofloxacin (0.54). However, other investigators (39,40), by detecting quinolones in the fluid of blisters, have demonstrated the ability of quinolones to penetrate the peripheral or tissue compartment. The blister fluid model represents a slow equilibrium model from a pharmacokinetic point of view.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrate a marked ofloxacin presence (53.48 ug/g) greater than that of pefloxacin (22.28 I1g/g) and ciprofloxacin (11.81 ug/g) in the parotid gland and are in agreement with Sorgel's findings of quinolones in the saliva: ofloxacin (0.89) >pefloxacin (0.54) >ciprofloxacin (0.54). However, other investigators (39,40), by detecting quinolones in the fluid of blisters, have demonstrated the ability of quinolones to penetrate the peripheral or tissue compartment. The blister fluid model represents a slow equilibrium model from a pharmacokinetic point of view.…”
Section: Discussionmentioning
confidence: 99%
“…Although similar in structure, various fluoroquinolones seem to differ in their pharmacokinetic properties and their pre dominant clearance pathways. Unlike ci- profloxacin, pcfloxacin and enoxacin that decrease the metabolic clearance of the ophylline, thus elevating it in plasma, lomefloxacin does not affect theophylline levels [Hunt and Adams, 1989;Morrison et al" 1988;Tartaglione et al, 1986;Wijnands et al, 1987;Wise et al, 1984;Wolf et al, 1984], Morrison et al [1988] reported max imum lomefloxacin serum levels of 1.11-7.46 pg/ml for the 100-to 800-mg oral dos es, respectively, and the serum half-life of approximately 8 h. These peak levels and the half-life of lomefloxacin provide the added advantage of possible single dosing per day as compared to twice-daily dosing for ciprofloxacin and norfloxacin. Several studies during the past few years have shown that lomefloxacin is ac tive against both gram-positive and gramnegative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Large filamentous forms as observed with ceph alosporins and gram-negative organisms [3] were not seen with ciprofloxacin. Un fortunately, the attainable serum concen trations of many of these compounds are low and are only a few fold above the MICs of many important pathogens [15]. Hence any factors which even modestly affect the ability of these compounds to in hibit or kill organisms might become clin ically important.…”
Section: Discussionmentioning
confidence: 99%
“…Since this class of compounds has re ported activity for the treatment of soft tis sue infections [8], urinary tract infections [5], and infections at other body sites by organisms often resistant to other antibiot ics [13], these agents might become an im portant class of anti-infective compounds. Unfortunately, the real limiting factor ap pears to be the attainment of therapeuti cally adequate tissue and blood levels of these compounds [15]. Therefore, we in vestigated the effects of pH and of diva lent cations on the results of quinolone susceptibility testing for the more com monly encountered bacterial pathogens.…”
Section: Introductionmentioning
confidence: 99%